Aripiprazole for the treatment of methamphetamine dependence: a randomized, double‐blind, placebo‐controlled trial. (3rd January 2013) - Coffin, Phillip Oliver; Santos, Glenn‐Milo; Das, Moupali; Santos, Deirdre M.; Huffaker, Shannon; Matheson, Tim; Gasper, James; Vittinghoff, Eric; Colfax, Grant N.
Abstract Aims To test aripiprazole for efficacy in decreasing use in methamphetamine‐dependent adults, compared to placebo. Design Participants were randomized to receive 12 weeks of aripiprazole or placebo, with a 3‐month follow‐up and a platform of weekly 30‐minute substance abuse counseling. Setting The trial was conducted from January 2009 to March 2012 at the San Francisco Department of Public Health. Participants Ninety actively using, methamphetamine‐dependent, sexually active adults were recruited from community venues. Measurements The primary outcome was regression estimated reductions in weekly methamphetamine‐positive urines. Secondary outcomes were study medication adherence [by self‐report and medication event monitoring systems (MEMS)], sexual risk behavior and abstinence from methamphetamine. Findings Participant mean age was 38.7 years, 87.8% were male, 50.0% white, 18.9% African American, and 16.7% Latino. Eighty‐three per cent of follow‐up visits and final visits were completed. By intent‐to‐treat, participants assigned to aripiprazole had similar reductions in methamphetamine‐positive urines as participants assigned to placebo [risk ratio (RR) 0.88, 95% confidence interval (CI): 0.66–1.19, P = 0.41]. Urine positivity declined from 73% (33 of 45 participants) to 45% (18 of 40) in the placebo arm and from 77% (34 of 44) to 44% (20 of 35) in the aripiprazole arm. Adherence by MEMS and self‐report was 42 and 74%, respectively, with no significant difference between arms (MEMS P = 0.31; self‐report P = 0.17). Most sexual risk behaviors declined similarly among participants in both arms (all P > 0.05). There were no serious adverse events related to study drug, although participants randomized to aripiprazole reported more akathisia, fatigue and drowsiness (P < 0.05). Conclusion Compared with placebo, aripiprazole did not reduce methamphetamine use significantly among actively using, dependent adults.